Dynamic Study of Bicycle Frame Structure - M. S. M., Sani; N. A., Nazri; S. N., Zahari; N. A. Z., Abdullah; G., Priyandoko (IOP Publishing, 2016)
Bicycle frames have to bear variety of loads and it is needed to ensure the frame can withstand dynamic loads to move. This paper focusing on dynamic study for bicycle frame structure with a purpose to avoid the problem regarding loads on the structure and to ensure the structure is safe when multiple loads are applied on it. The main objectives of dynamic study are to find the modal properties using two method; finite element analysis (FEA) and experimental modal analysis (EMA). The correlation between two studies will be obtained using percentage error. Firstly, 3D model of mountain bike frame structure has been draw using computer-aided design (CAD) software and normal mode analysis using MSC Nastran Patran was executed for numerical method meanwhile modal testing using impact hammer was performed for experimental counterpart. From the correlation result, it show that percentage error between FEA and EMA were below 10% due to noise, imperfect experiment setup during perform EMA and imperfect modeling of mountain bike frame structure in CAD software. Small percentage error differences makes both of the method can be applied to obtain the dynamic characteristic of structure. It is essential to determine whether the structure is safe or not. In conclusion, model updating method is required to reduce more percentage error between two results.